Decorative cermet article
A cermet composition with noble metal binders and oxides/oxynitrides addresses the issues of allergenic metals and production challenges, achieving high hardness and durability for decorative items.
Patent Information
- Application Number
- JP2024166185
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-09-09
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-07-07
AI Technical Summary
Existing cermet materials used in watch cases and jewelry contain allergenic metals like nickel and cobalt, and are difficult to produce with high hardness and durability due to poor wettability and high melting points, leading to porosity and reduced hardness during sintering.
A cermet composition comprising 70-97% ceramic phase and 3-30% metal binder phase, using noble metals like ruthenium, rhodium, and platinum, with optional oxides and oxynitrides to enhance hardness and toughness, produced through powder metallurgy and liquid phase sintering under low pressure.
The developed cermet achieves high scratch resistance (500-1,250 HV30), toughness, and a metallic luster comparable to stainless steel, suitable for 'near net shape' 3D parts with a color tone from white to yellow, overcoming the limitations of conventional sintering methods.
Smart Images

Figure 2024178385000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a decorative item made of a cermet-type material, in particular for timepieces. Cermet-type materials are made up of a ceramic phase with nitrides and a noble phase with and a metallic phase comprising a metal. [Background technology]
[0002] Nitride-based colored cermets are free of allergy-inducing metal bonds such as nickel or cobalt. Contains a combination of drugs. The watch case or jewelry, etc., are manufactured with parts that may come into contact with the skin. In order to manufacture such materials, it is essential to develop compositions that do not use binders that contain these elements. be.
[0003] In addition, cermets used for specific applications such as watch cases have extremely high resistance It must be scratch resistant, i.e. have a hardness of more than 1,000 HV. There is a need to reduce the amount of metal binder while controlling the wettability between the metal binder and the ceramic phase. Poor wettability reduces the density of the final product and therefore reduces its hardness. contains nickel and cobalt free, and has excellent final properties. It is difficult to produce colored cermets of the N series by powder metallurgy and conventional liquid phase sintering. This is mainly because titanium nitride has a very high melting point of 2,930°C, and the melting point of the metal during liquid phase sintering is This is due to poor wettability with the binder. As a result, the cermet is porous at the end of sintering. increases and the hardness decreases.
[0004] In addition to hardness, the different phases are mixed so that high toughness and the desired color are obtained in the final product. The ratios also need to be adjusted. Summary of the Invention
[0005] The object of the present invention is to propose a cermet having an optimal composition that satisfies the following criteria: It is to overcome the shortcomings. -Does not contain allergenic elements such as nickel or cobalt, - Densification is possible by liquid phase sintering under low pressure (conventional sintering), For applications where very high scratch resistance is required, preferably 2.8 MPa.m 1 / 2 Below K above iC While having sufficient toughness, the hardness should be at least 500HV30, preferably at most having a minimum hardness of 550 HV30, more preferably a minimum hardness of 1,000 HV30; -It has a white to yellow color and a high metallic luster (65 <L*≦80)。
[0006] Therefore, the present invention proposes a decorative item made of a cermet material. The material comprises 70 to 97 weight percent ceramic phase and 3 to 30 weight percent metal binder phase. Metal binders include ruthenium, rhodium, palladium, osmium, iridium, and platinum. At least one element selected from the list consisting of nickel, gold and silver or an alloy thereof. The ceramic phase includes a nitride phase and, optionally, an oxide phase and / or an oxynitride phase. The nitride phase is present in a proportion of 70 to 97% by weight of the total weight of the cermet material, and the oxide phase is The nitride and / or oxynitride phases are present in an amount of 0 to 15% by weight.
[0007] Specifically, a yellow titanium nitride (TiN) based cermet was fabricated using powder metallurgy and conventional liquid phase sintering. To produce a dense sintered body, oxides and / or oxynitrides are added. It is proposed that this promotes hardening and increases hardness.
[0008] The cermet material developed in this way is polished and then bonded with nickel or It has a metallic luster that exceeds that of cobalt-based cermets and is comparable to that of stainless steel. These valuable cermets have a strength of up to 1,250HV30. It has a hardness that can be easily broken down and is tough enough to manufacture external components. These cermets are used to obtain 3D parts with a near-net shape close to the finished product. It can be formed by conventional powder metallurgy methods such as compression or injection.
[0009] Further characteristics and advantages of the present invention will become apparent from the following description, given as a non-limiting example, with reference to the accompanying drawings, in which: This will become apparent from the following description of the preferred embodiments. [Brief description of the drawings]
[0010] [Figure 1] 1 shows a timepiece with a body made of a cermet-type material according to the invention. [Diagram 2] 1 shows an optical microscope image of a cermet type material according to the invention having a composition by weight of 92% TiN and 8% Pd. [Diagram 3] 1 shows an optical microscope image of a cermet type material according to the present invention having a composition by weight of 84.6% TiN, 9.4% zirconium oxide (ZrO2), and 6% Pd. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention relates to a decorative item made of a cermet-type material. The material contains 70 to 97% by weight of a ceramic phase and 3 to 30% by weight of a metal binder phase. Preferably, the cermet comprises 75 to 97% by weight of a ceramic phase, and 3 to 25 wt. % of a metal binder phase. More preferably, the cermet comprises %, 78 to 96 wt. % of a ceramic phase and 4 to 22 wt. % of a metal binder phase (or The metal binder is selected from the group consisting of ruthenium, rhodium, palladium, osmium, and iridium. The metal binder may also be selected from the list of elements comprising platinum, gold and silver. For example, Au-3N, Au-5N, or a combination of these elements. The ceramic phase may be a combination of an alloy of one of the elements. Optionally, the ceramic phase may comprise an oxide phase and / or an oxynitride phase. In other words, the ceramic phase may comprise a nitride phase. and optionally an oxide and / or an oxynitride phase. The purpose of the oxynitride phase is to increase the mechanical properties. When nitride phases are present, the oxide and / or oxynitride phases are less than the nitride phase. Specifically, the nitride phase is present in an amount of 70 to 97% by weight based on the total weight of the cermet. The oxide and oxynitride phases are present in amounts ranging from 0 to 15 wt. %. The nitrides are Al, Ti, Si, Mn, Zr, Hf, Ta, Nb, V, Cr, Mo, W, B nitrides, and The oxides and oxides are selected from a non-exclusive list including combinations of nitrides of these elements. The nitrides are Al, Ti, Si, Mn, Zr, Hf, Ta, Nb, V, Cr, and M. O, W, B oxides and oxynitrides, and combinations of oxides and oxynitrides of these elements The combination is selected from a non-exclusive list including:
[0012] The ornamental item may be a component part of a watch, a piece of jewelry, a bracelet, and the like. In the field of watch manufacturing, decorative items include the body, back, bezel, crown, bracelet, etc. The external parts may be rings, dials, hands, indexes of the dial, etc. FIG. 1 shows a body portion 1 made of a cermet-type material according to the present invention.
[0013] Cermet items start as a mixture of ceramic and metal powders and are manufactured by sintering. The manufacturing method includes the following steps: a) Producing a mixture of different powders, possibly in a moist environment. The diameter (d50) of the particles is preferably less than 10 μm, more preferably between 2 and 5 μm. The mixture may be produced in a mill, if possible, so that after milling The d50 of the powder particles is reduced to a size of about a micron or even less than a micron. The mixture is preferably from 70 to 97% by weight, more preferably from 75 to 97% by weight, and even more preferably from 75 to 97% by weight. The ceramic powder preferably contains 78 to 96% by weight of ceramic powder, and more preferably contains 3 to 30% by weight of ceramic powder, and more preferably contains 3 to 30% by weight of ceramic powder. 25% by weight, more preferably 4 to 22% by weight of metal powder. The ceramic powder is preferably nitrided. More specifically, the total weight of the powder is The nitride is 70 to 97% by weight, preferably 75 to 97% by weight, more preferably 75 to 97% by weight. 8 to 96% by weight, and oxides and / or oxynitrides are present in an amount of 0 to 15% by weight. The nitrides are Al, Ti, Si, Mn, Zr, Hf, Ta, Nb, V, C A non-exclusive list including R, Mo, W, B nitrides and combinations of nitrides of these elements. Advantageously, the nitrides are selected from Ti, Ta, Nb, Zr nitrides and their elements. The oxide and oxynitride are selected from a combination of Al, T, I, Si, Mn, Zr, Hf, Ta, Nb, V, Cr, Mo, W, B oxides and oxynitrides From a non-exclusive list including combinations of oxides and oxynitrides of these elements: Advantageously, the oxides and oxynitrides are Zr or Nb oxides and oxynitrides. The metal powder is selected from ruthenium, rhodium, palladium, osmium, iridium, Metallic elements including zinc, platinum, gold, and silver, combinations of these elements, and The elements are selected from the list of alloys of one of the elements. Thus, preferably, gold is selected from the list of alloys of one of the elements, Cu, It is an alloy with at least one element selected from Ag, Pd, C, N. Advantageously, gold The metal powders primarily include palladium, platinum, silver, or gold alloyed with copper and / or silver. The metal powder, apart from impurities, is composed of platinum, palladium, silver, or copper and / or silver. As an example, the powder mixture may consist entirely of alloyed gold, with the following weight distribution: It may contain one of them. - 78 to 96 wt. % TiN and 5 to 20 wt. % Pd or Pt; - 80 to 90 wt. % TiN and 10 to 20 wt. % Ag, - 75 to 85 wt. % TiN and 15 to 25 wt. % Au alloy; - 80 to 90 wt. % niobium nitride (NbN) and 10 to 20 wt. % Au alloy; - 85 to 95 wt.% NbN or Tantalum Nitride (TaN) and 5 to 15 wt.% Pd or Pt, -80 to 90 wt.% TiN, 5 to 15 wt.% ZrO2, and 3 to 10 wt.% % Pd or Au alloy, - 75 to 85 wt.% TiN, 5 to 15 wt.% zirconium nitride (ZrN), and and 5 to 15 wt. % Au alloy, - 70 to 80 wt.% NbN, 5 to 20 wt.% niobium pentoxide (Nb2O5), and and 5 to 15 wt. % Pt. b) Optionally, a mixture of the above with an organic binder system (paraffin, polyethylene, etc.) A second mixture can be created. c) The mixture is then molded as desired, for example by injection (ceramic injection molding) or compression. The step of forming a blank into the shape of an item. d) From 1,100 to 2,100°C under inert atmosphere, nitrogen or vacuum At a temperature of preferably 1,400 to 1,750°C for 30 minutes to 20 hours sintering the blank, preferably for a period of 30 minutes to 2 hours. If the system contains a ferroelectric material, it is debonded at a temperature in the range of 200 to 800°C prior to this step. This step may be preceded by a step of:
[0014] The blank thus obtained is cooled and polished. The blank may be machined prior to polishing.
[0015] The item obtained from this manufacturing method has a ceramic phase and a metallic phase. is close to the weight percent of the starting powder. However, it may change due to contamination or alteration during sintering, for example. Small variations in composition and proportions may occur between the raw powder and the material obtained by sintering. For example, if the starting powder contains both nitrides and oxides of the same element, the oxide Nitrides may also be formed in situ. Metallic and ceramic phases are present in cermet materials. Evenly distributed.
[0016] The item complies with the International Commission on Illumination (CIE) Standard No. 15, lSO7724 / 1, Germany According to industrial standards (DIN) 5033 Teil 7, ASTM E-1164), the lightness of the material The lightness L* component, which indicates the reflectance of the The CIELAB color space is 75. The color ranges from white, which corresponds to steel color, to It can range from a slight yellowish color to a strong yellow color. More specifically, white For this item, the a* component is between -3 and +3, and the b* component is between -3 and +3. For colors between white and yellow, the a* component is between 0 and +3, and the b* component is between 0 and +1. 0. For yellow, the a* component is between 0 and +5, and the b* component is between +20 and +3 0.
[0017] Ceramic materials are measured under a load of 30 kg (HV30) to determine the type and proportion of constituents. Depending on the material, the Vickers hardness is 500 to 1,300, preferably 550 to 1,250. Advantageously, ceramic materials are used for external parts where very high scratch resistance is required. ,000 Vickers hardness. Ceramic materials have a minimum hardness of 2 MPa.m 1 / 2 , preferably a minimum of 2.8 MPa.m 1 / 2 The toughness of iC The resilience is The hardness is determined based on the measurement of the crack length at the four ends of the diagonal of the hardness indentation according to the formula It is determined.
[0018]
number
[0019] where P is the applied load (N), a is the half diagonal (m), and l is the measured is the length of the crack (m).
[0020] Table 1 below contains various examples of cermets according to the invention. The values in italics and bold are: Hardness over 1,000 Vickers, 2.8MPa.m 1 / 2 Toughness exceeding 100%, deep yellow Meet the criteria of L* index greater than 75 or b* index greater than 25 for.
[0021] Thirteen mixtures of powders of different compositions were prepared in a mill in the presence of a solvent. It was produced without the addition of a binder. After drying, the mixture was pressed into a mold by uniaxial compression and sintered in a vacuum. The powders were then cooled to room temperature, depending on the powder composition, under a dynamic partial pressure of 60 mbar of argon or nitrogen. After sintering, the samples were flattened to accurately measure the mechanical properties and color index. Polished to.
[0022] HV30 hardness measurements were performed on the surface of the samples and the toughness was determined based on the aforementioned hardness measurements.
[0023] The Lab color measurement values of the polished samples were measured using a KONICA MINOLTA CM-5 spectrophotometer. Using the 8° inclination, SCI (specular reflection included) and SCE (specular reflection excluded) measurements were performed. Measurements were performed under conditions of a MAV measurement zone with a diameter of 8 mm.
[0024] From these tests, it was found that hardness exceeding 1,000 Vickers can be obtained with the following composition. TiN 84.6%, ZrO 29.4%, Pd 6% (Test No. 3), Nb N89.5%, Pd10.5% (Test No. 4), TaN89.5%, Pd10.5% (Test No. Test No. 5), TiN85%, Pt15% (Test No. 6), NbN75%, Nb2O515 %, Pt10% (Test No. 8), TiN84.6%, ZrO29.4%, Au3N6%( Test No. 9), NbN 86%, Au 10.5%, Cu 3.5% (Test No. 12). The same composition is 3.3MPa.m 1 / 2 It has a toughness that exceeds
[0025] Specifically, test number 2 (TiN 92%, Pd 8%) and test number 3 (TiN 84.6% , ZrO2 9.4%, Pd 6%), the addition of oxide in the case of ZrO2 In the case of the annealed specimen, the Vickers hardness clearly increases from 590 to 1,050. Oxides can improve densification and they enhance mechanical properties. In Fig. 3, when oxide is added to sample No. 3, the same amount of oxide as in Fig. 2 is added to the sample No. A reduction in porosity (black spots) is observed compared to sample No. 2. Thus, there is a significant effect on toughness. Similarly, comparing test number 7 and test number 8, the hardness is almost doubled without any By adding Nb2O5, an increase in hardness and toughness is observed.
[0026] Furthermore, the combination of NbN and gold alloy (test number 12) resulted in a 1,000 Vica Hardness values exceeding 4.5MPa.m 1 / 2 Toughness exceeding 80 and brightness L* approaching 80 It is possible to combine this with polished stainless steel to achieve the same value, i.e. the same brightness.
[0027] When platinum (sample no. 6) is used as a binder instead of palladium (sample no. 1), This difference, which contains 85% TiN, allows a maximum hardness of 1,192 Vickers to be reached. It can be seen that the hardness increases as the
[0028] [Table 1] *Au-3N: Au75%, Ag12.5%, Cu12.5%, Addition Table 1
Claims
1. A decorative item made of a cermet material, the cermet material having a hardness of 70 to 97 % by weight of a ceramic phase and 3 to 25% by weight of a metal binder phase, said metal binder being , ruthenium, rhodium, palladium, osmium, iridium, platinum, gold and silver At least one element or alloy thereof selected from the list consisting of The sintered phase comprises a nitride phase and, optionally, an oxide phase and / or an oxynitride phase, The nitride phase is present in an amount of 70 to 97% by weight based on the total weight of the metal material. The oxide and / or oxynitride phases are present in an amount of 0 to 15% by weight. Hmm.
2. 2. The item of claim 1, wherein the metal binder phase is present in an amount of 4 to 22 weight percent. The ceramic phase is present in an amount of 78 to 96% by weight, and the total weight of the cermet material is The nitride phase is present in an amount of 78 to 96% by weight, and the oxide phase and The oxynitride phase and / or oxynitride phase are present in an amount of 0 to 15% by weight. Hmm.
3. 3. The item of claim 1 or 2, wherein the nitride phase is selected from the group consisting of Al, Ti, S Selected from the list of i, Mn, Zr, Hf, Ta, Nb, V, Cr, Mo, W, B nitrides.
23. An item comprising one or more nitrides.
4. 4. The item of claim 3, wherein the nitride is selected from the group consisting of Al, Si, Ti, Ta, Nb, The item, characterized in that the metal oxide is selected from Zr nitrides.
5. 5. An item according to any one of claims 1 to 4, wherein the oxide and acid are The nitrides are Al, Ti, Si, Mn, Zr, Hf, Ta, Nb, V, Cr, and M. O, W, B oxides and oxynitrides and combinations of oxides and oxynitrides of these elements and wherein the item is selected from a list comprising:
6. 6. The item of claim 5, wherein the oxides and oxynitrides are selected from the group consisting of Al, Si, Ti, , Ta, Nb, Zr oxides and oxynitrides.
7. 7. The item of claim 6, wherein the ceramic phase is a Ti nitride phase and a Zr oxide phase.
16. An item comprising a compound phase.
8. 7. The item of claim 6, wherein the ceramic phase comprises a Nb nitride phase and a Nb oxide phase.
16. An item comprising a compound phase.
9. 9. The item of any one of claims 1 to 8, wherein the metal binder phase comprises , characterized in that it is made of palladium, platinum, silver or gold alloy, excluding impurities. ,item.
10. 10. The item of any one of claims 1 to 9, wherein the metal binder phase comprises The gold alloy includes one or more metals selected from copper, silver, palladium, and nitrogen. An item characterized by comprising a number of elements.
11. 11. An item according to any one of claims 1 to 10, comprising: 00, preferably 550 to 1,250 Vickers hardness HV30. item.
12. 12. An item according to any one of claims 1 to 11, The ceramic phase comprises Ti nitrides and Zr oxides, and the metal binder phase comprises Pd or or Au alloy, the ceramic phase comprises Ta or Nb nitrides and the metallic binder phase comprises Pd tree, when the ceramic phase comprises Ti nitride and the metallic binder phase comprises Pt, - the ceramic phase comprises Nb nitrides, Nb oxides and the metal binder phase comprises Pt When, when the ceramic phase comprises Nb nitrides and the metallic binder phase comprises Au alloys, 1. An item characterized by having a Vickers hardness HV30 of greater than 1,000.
13. 13. An item according to any one of claims 1 to 12, having a strength of 2.8MPa.m 1/2 More than tough K iC An item comprising:
14. 14. An item according to any one of claims 1 to 13, in the CIELAB colour space. Between the above, the L* component is at least 60, preferably at least 65, and more preferably at least 75. An item, characterized in that
15. 15. An item according to any one of claims 1 to 14, which is yellow in colour and has a C.I. In the ELAB color space, the a* component ranges from 0 to +5, and the b* component ranges from +20 to +3.
0.
16. 15. An item according to any one of claims 1 to 14, which is white in colour and has a C.I. In the ELAB color space, the a* component ranges from -3 to +3, and the b* component ranges from -3 to +3. An item characterized in that it is between.
17. 15. An item according to any one of claims 1 to 14, which is between white and yellow. In the CIELAB color space, the a* component is between 0 and +3, and the b* component is An item characterized by being between 0 and +10.
18. 18. The item according to any one of claims 1 to 17, comprising a body, a back cover, a bezel, The watch features a crown, bracelet links, dial, hands and dial indexes. An item characterized in that it relates to a component part of an external timer selected from a list.
19. A method for manufacturing a decorative item, comprising the steps of: a) preparing a mixture of ceramic powder and metal binder powder, The tungsten carbide powder comprises nitrides and, optionally, oxides and / or oxynitrides, and is provided with a metal binder. The powders are ruthenium, rhodium, palladium, osmium, iridium, platinum, gold, providing at least one element selected from the list consisting of silver or an alloy thereof; and, b) forming a blank into which said mixture is shaped into said item; c) at a temperature of from 1,100 to 2,100° C., preferably from 1,400 to 1,750° C. The bran is heated at a temperature of up to 30° C. for 30 minutes to 20 hours, preferably for 30 minutes to 2 hours. sintering the ink; A method comprising the successive steps of: In the method, the ceramic powder is 70 to 97% by weight, preferably 75 to 9 7% by weight, more preferably 78 to 96% by weight, and the metal binder powder is present in an amount of 3 to 25% by weight. %, more preferably from 4 to 22% by weight.
20. 20. The method of claim 19, wherein the mixture of step a) comprises: - 78 to 96 wt. % TiN and 4 to 22 wt. % Pd or Pt; - 80 to 90 wt. % TiN and 10 to 20 wt. % Ag; - 75 to 85 wt. % TiN and 15 to 25 wt. % Au alloy; - 80 to 90 wt. % NbN and 10 to 20 wt. % Au alloy; - 85 to 95 wt. % NbN or TaN and 5 to 15 wt. % Pd or Pt; - 80 to 90 wt. % TiN and 5 to 15 wt. % ZrO 2 and 3 to 10 wt.% Pd or Au alloy of - 75 to 85 wt. % TiN, 5 to 15 wt. % ZrN, and 5 to 15 wt. % Au alloy, - 70 to 80 wt.% NbN and 5 to 20 wt.% Nb 2 O 5 and 5 to 15 wt. % Pt, The method of claim 1, further comprising the steps of:
21. 21. The method according to claim 19 or 20, wherein step b) comprises compression or injection. The method according to claim 1, characterized in that it is carried out by
Citation Information
Patent Citations
JP1973034709A
JP1973038211A
JP1973079110A
JP1973083013A
Sintered noble metallic alloy with wear resistance
JP1982026136A
